DISENTANGLING THE VARYING ASSOCIATIONS BETWEEN SYSTOLIC BLOOD PRESSURE AND HEALTH OUTCOMES IN THE VERY OLD: AN INDIVIDUAL PATIENT DATA META-ANALYSIS. (June 2022) - Bogaerts, Jonathan; Poortvliet, Rosalinde; Van Der Klei, Veerle; Achterberg, Wilco; Blom, Jeanet; Teh, Ruth; Muru-Lanning, Marama; Kerse, Ngaire; Rolleston, Anna; Jagger, Carol; Kingston, Andrew; Robinson, Louise; et al.
Abstract : Objective: While randomized controlled trials have proven the benefits of blood pressure (BP) lowering in participating octogenarians, population-based observational studies suggest an association between low systolic blood pressure (SBP) and faster overall decline. This study investigates the effects of BP-lowering treatment, a history of cardiovascular diseases (CVD), and cognitive and physical fitness on the associations between SBP and health outcomes in the very old. Design and method: Five cohorts from the Towards Understanding Longitudinal International older People Studies (TULIPS) consortium were included in a two-step individual participant data meta-analysis (IPDMA). We pooled hazard ratios (HR) from Cox proportional-hazards models for five-year mortality and estimates of linear mixed models for change in cognitive and functional decline. Models were stratified by BP-lowering treatment, history of CVD, Mini-Mental State examination-scores (MMSE) and grip strength (GS). Results: Of all 2480 participants (59.9% females, median 85 years), median baseline SBP was 149 mmHg, 64.3% used BP-lowering drugs and 47.3% had a history of CVD. Overall, higher SBP was associated with lower all-cause mortality (pooled HR 0.91 [95%CI 0.88–0.95] per 10 mmHg). Associations remained irrespective of BP-lowering treatment and history of CVD, but were absent in octogenarians with above-median MMSE and GS. In pooled cohorts, SBP was not associated with cognitive and functional decline. Conclusions: While in the very old with low cognitive or physical fitness, a higher SBP was associated with a lower all-cause mortality, this association was not evident in fit octogenarians. SBP was not consistently associated with cognitive and functional decline.